The role of task sequencing in fluency, accuracy, and complexity: Investigating the SSARC model of pedagogic task sequencing. (September 2020) - Malicka, Aleksandra
This study set out to test the theoretical premise of the SSARC model of pedagogic task sequencing, which postulates that tasks should be sequenced for learners from cognitively simple to complex. This experiment compared the performance of three tasks differing in cognitive complexity in a simple–complex sequence versus in the absence of any other tasks. There were two groups in the study: (1) participants who performed the three tasks in the simple–complex sequence, and (2) participants who performed either the simple, the complex, or the most complex task. The participants' speech was analysed using fluency, accuracy, and complexity measures. The results indicate that simple–complex sequencing led to a higher speech rate, greater dysfluency, enhanced accuracy, and greater structural complexity, as compared to individual task performance. The results are discussed in terms of the SSARC model and pedagogical implications of the findings are presented.